2022
DOI: 10.3389/fnut.2022.935865
|View full text |Cite
|
Sign up to set email alerts
|

Association between chili pepper consumption and risk of gastrointestinal-tract cancers: A meta-analysis

Abstract: BackgroundStimulating food is emerging as an important modifiable factor in the development of gastrointestinal (GI) tract cancers, but the association between chili pepper consumption and the risk of GI cancers is unclear. We aimed to evaluate the direction and magnitude of the association between chili pepper consumption and the risk of GI cancers.MethodsA literature search was performed in PubMed, Embase, and Web of Science databases from inception to 22 December 2021. Observational studies reporting the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Stimulating food is one of the factor in the development of gastrointestinal tract cancers, with unclear association between chili pepper consumption and the risk of cancer. Chen et al [ 68 ] found that geographic regions influence gastrointestinal cancer risk, particularly in Asian, African, and North American populations, which require greater attention during dietary counseling.…”
Section: Resultsmentioning
confidence: 99%
“…Stimulating food is one of the factor in the development of gastrointestinal tract cancers, with unclear association between chili pepper consumption and the risk of cancer. Chen et al [ 68 ] found that geographic regions influence gastrointestinal cancer risk, particularly in Asian, African, and North American populations, which require greater attention during dietary counseling.…”
Section: Resultsmentioning
confidence: 99%
“…In a case-control study, it was also shown that people who consumed chili peppers had a higher risk of GC than non-consumers [88]. The opposite conclusion was reached by Changchang et al [142]; in their meta-analysis, they found no association between chili pepper consumption and increased GC risk [142]. The effect of capsaicin on the development of GC requires further research.…”
Section: Chili Peppermentioning
confidence: 95%